2019
DOI: 10.1021/acs.jafc.9b04952
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Glucosinolate Thermal Degradation and Roasted Rapeseed Oil Volatile Odor

Abstract: This study aims to investigate the effect of glucosinolate (GSL) degradation on the volatile odor of rapeseed oil (RO) during roasting. Volatile compounds of RO and individual GSL contents in the seeds were identified and measured during roasting, separately. Total GSL content decreased by 30.47–84.44%. Nitriles were the key volatile compounds that were negatively correlated with GSLs for all samples. Results indicate that GSL degradation significantly affects the volatile odor of RO and tends to produce low-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…Rapeseed oils are considered the third largest edible oil source in the world with growing demand and production (Mao et al., 2019). Most rapeseed oils are produced as refined oils with slight flavor and degraded nutritional components, and therefore virgin rapeseed oils (VROs) concentrate growing concern from consumers currently (Kraljić et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rapeseed oils are considered the third largest edible oil source in the world with growing demand and production (Mao et al., 2019). Most rapeseed oils are produced as refined oils with slight flavor and degraded nutritional components, and therefore virgin rapeseed oils (VROs) concentrate growing concern from consumers currently (Kraljić et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mao et al. (2019) confirmed that hexanal, nonanal, and octanal were dominant volatiles in non‐roasted rapeseed oil, which were related to the grassy and fatty smelling. Hexanal, heptanal, ( E )‐2‐hexenal, ( E , E )‐2,4‐decadienal, and benzaldehyde were reported to be aroma‐active compounds in commercial fragrant rapeseed oils (virgin rapeseed oil obtained from roasted seeds) (Zhou et al., 2019).…”
Section: Flavor Compounds In Rapeseed Oilmentioning
confidence: 96%
“…( E , Z )‐2,6‐Nonadienal is known to be derived from 9‐hydroperoxy‐( E , Z , Z )‐10,12,15‐octadecatrienoic acid. 2‐Methylbutanal, 3‐methylbutanal, and 2‐methylpropanal, related to a malty odor in oil, are generated by Strecker degradation of the corresponding amino acids isoleucine, leucine, and valine during roasting of the seeds (Bonte et al., 2017; Gracka et al., 2016; Mao et al., 2019; Matheis & Granvogl, 2016a; Pollner & Schieberle, 2016; Zhou et al., 2019).…”
Section: Flavor Compounds In Rapeseed Oilmentioning
confidence: 99%
See 2 more Smart Citations